Decomposition of gendered socioeconomic‐related inequality in outpatient health care utilization: A cross‐sectional study from Iran. (8th January 2021) - Vahedi, Sajad; Ramezani‐Doroh, Vajiheh; Shamsadiny, Mohammad; Rezapour, Aziz
Abstract: Introduction: Unequal access to required health care services could deteriorate inequality in health outcomes and increase mortality and morbidity, especially among disadvantaged groups. One of the most debated factors in shaping health care inequalities is gender. This study aimed to measure and explains gendered socioeconomic‐related inequality in outpatient health care utilization in Iran. Methods: This is a cross‐sectional research conducted at a national level in Iran. The required data was obtained from an Iranian health care utilization household survey conducted in 2015. Erreygers Concentration Index (ECI) was used to measure the socioeconomic inequality in outpatient health care utilization. A regression‐based decomposition analysis was also used to explain socioeconomic‐related inequalities. Results: There was a significant pro‐rich inequality in outpatient health care utilization between males (ECI = 0.115, SE = 0.014) and females (ECI = 0.083 SE = 0.011) indicating that utilization of these services was concentrated on the better‐offs. The decomposition analysis revealed that economic status (males = 50.58%, females = 37.42%) was the main contributor to the observed inequality. Location of residence, health insurance and education were other main driver of these inequalities. Conclusions: Different factors have different contribution to socioeconomic‐related inequality in utilization of outpatient health care services and these could be diversified considering gender. Hence, it seems that policy makers could be able to address these inequalities effectively through gender‐oriented policies.